Modeling the depth of chloride ingress and time-to-initiate rebar corrosion in concretes exposed to tiodal zone - Anacta, Ernesto Tan (2009)
Chloride -induced corrosion of steel in concrete is undoubtedly the most damaging type of deterioration faced by structures exposed to marine environment. In the Philippines where over 75% of the structures are located in this aggressive location, seawater-initiated corrosion had become a common problem to bridges, ports, and other near-shoreline structures, causing their deterioration and costing millions of pesos in terms of repair and maintenance every year.
To lessen the impact of this problem, a study on the effect of blended cements and water-cement ratio on chloride ingress and time-to-initiate corrosion was conducted, the purpose of which is to develop a prediction model that will help in extending the service life of these sea-based structures and minimize their post-construction costs.
In this study, 12 types concretes consisting of four blended cements (OPC with 0, 10, 20, and 30 percent fly ash replacements) and three water-cement ratios (0.40, 0.55 and 0.70) were used. For 12 months, these concretes were subjected to three types of exposures (laboratory wet, laboratory wet/dry and sea-tidal conditions) in a 3.5 percent saline environment, measuring the depth of chloride penetration every month. In addition, a 4-month laboratory experiment whose purpose is to determine the time-to-initiate corrosion of steel on the same set of specimens was also conducted.
Results have shown that concretes with more fly ash and less water-cement ratio have better resistance to chloride penetration which translate to longer pre-corrosion period. Based on the two experiments, a prediction model which uses both material and environmental parameters and based on Philippine setting was developed. The said model agrees well with existing models found in literatures and can be very useful in the area of construction and maintenance of marine structures.
Dissertation (PhD Civil Engineering)--University of the Philippines Diliman.
Keywords: Chloride ingress